The Influence of Previous Treatment of Wheat Straw from Bales on the Intensity of Biogas Outlet - Zablodskiy M.; Klendiy P.; Shvorov S.; Trokhaniak V.; Dudar O. (Problems of the Regional Energetics)
The purpose of the research is the experimental determination of the effect of preliminary mechanical and additional magnetic treatment of wheat straw from bales on the intensity of biogas output. This goal is achieved by solving the following problems: determining the physical-chemical properties and component composition of winter wheat straw from packs; obtaining chopped straw by grinding on a laboratory grinder to a fraction of 5–25 mm in length; processing soaked straw in water in an extruder to form 15 pre-treatment samples; calculation the carbon-nitrogen ratio for mixture of straw of certain pretreatment option and inoculum; determination the specific energy intensity of the extrusion process; conducting fermentation experiments and studies of the biogas output process for 42 days for various options for pre-treatment of winter wheat straw from packs, in particular the option with the simultaneous action of constant magnetic field. The most important results of the research are: experimental proof of the effectiveness of the method of preliminary mechanical-magnetic treatment of winter wheat straw from bales in the production of biogas, which forms a synergetic effect; with a one-time extrusion of straw and treatment with constant magnetic field of 1.8 mT, the biogas output increases, which makes it possible to obtain the same amount of biogas as with 5-fold extrusion, but with energy costs for extrusion reduced by 4.28 times. At the same time, sufficient productivity of the biogas production process is maintained, the lag phase is reduced, and the biomethane output increases by approximately 5.5%. The significance of the obtained results is that the proposed approach to the formation of biogas technology with using mechanical-magnetic processing of wheat straw ensures the intensification of biogas output and an increase in the level of production.